PENGALAMAN KOMUNIKASI DAN KONSEP DIRI PEREMPUAN GEMUK - Welly Wirman (Indonesian Journal of Dialectics, 2012)
Experience Construction of Communications and Self-concept of Fat Women in Pekanbaru, Riau in phenomenological perspective, aiming to uncover the experience of interpersonal communication and self-concept of obese women, obese women motives in the effort to achieve ideal body weight, and to know how they interpret the meaning of fat.This study uses qualitative research as approach, constructivism as paradigm and phenomenology as the type of study. The research subjects were 15 obese women in Pekanbaru that have been purposively selected. To collect the data this study used in-depth interviews, observation and literature study methods.The results revealed that: the experience of communication associated with overweight women include obesity, pleasant communication experience, and experience the unpleasant communication. This is a result of interaction with family, environmental education, employment and the opposite sex.Participants who have overweight at the age of children to adolescence have more positive self-concept. Otherwisefor the adults they tend to have negative self-concept. There are three categories of self-concept of obese women 1) Positive view of self, physically, psychologically and socially; 2) negative view of self physically and psychologically, but socially positive, 3). negative view of self physically, psychologically and socially.Many obese women try to lose their weight, it its motivated by the reason of fitnes for healthy life, and reason of freshnes for body appearance. The motivation source of to lose weight some participants derived from personal motives and the othersfrom social motives.